2001
DOI: 10.1002/mc.1023
|View full text |Cite
|
Sign up to set email alerts
|

Two consistently deleted regions within chromosome 1p32‐pter in human non–small cell lung cancer

Abstract: Allelic losses at 1p32-pter have been reported as frequent events in human non-small cell lung cancer (NSCLC). To further characterize the region of deletions, we studied loss of heterozygosity on a panel of 102 microdissected NSCLC samples with 20 polymorphic markers spanning 1p32-pter. Two shortest regions of the overlap of the deletions (SROs) were found: SRO 2a (D1S417--D1S57) and SRO 2b (D1S450--D1S243). Allelic losses at either region correlated independently with advanced stage of disease and with posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Receptor-interacting serine-threonine kinase (RIPK) 3, which is part of the same family as RIPK1, which contains a death domain, has never been reported to be hypermethylated in any cancers before our report. Interestingly, the locations of HIC1, RIPK3, FABP3, and PRKCDBP were reported to lose heterozygosity in lung cancer (Konishi et al 1998;Abujiang et al 1998;Chizhikov et al 2001;Petersen et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Receptor-interacting serine-threonine kinase (RIPK) 3, which is part of the same family as RIPK1, which contains a death domain, has never been reported to be hypermethylated in any cancers before our report. Interestingly, the locations of HIC1, RIPK3, FABP3, and PRKCDBP were reported to lose heterozygosity in lung cancer (Konishi et al 1998;Abujiang et al 1998;Chizhikov et al 2001;Petersen et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant expression of Plk3 is found in multiple tumors (5, 6). The human PLK3 gene is localized to the short arm of the chromosome 1 (1p32), a region that displays loss of heterozygosity or homozygous deletions in many types of cancer and has been proposed to harbor tumor susceptibility genes (7,8). A recent mouse genetic study showed that PLK3 Ϫ/Ϫ mice develop tumors in multiple organs at an enhanced rate (4).…”
mentioning
confidence: 99%
“…Multiple regions on this chromosome arm have been implicated in SCLC and non-small-cell lung cancer (NSCLC) (Girard et al, 2000;Nomoto et al, 2000;Chizhikov et al, 2001;Ashman et al, 2002). Here, we describe the construction of a unique resource for analysing 1p.…”
mentioning
confidence: 99%